2010
DOI: 10.1007/s11240-010-9827-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphomannose-isomerase as a selectable marker to recover transgenic orchid plants (Oncidium Gower Ramsey)

Abstract: A transformation method using the phosphomannose-isomerase (pmi) gene as a selectable marker was developed for orchid Oncidium Gower Ramsey. The pmigene, which converts mannose-6-phosphate to fructose-6-phosphate allowing for selection of transgenic plants on mannose selective medium. Genetically transformed plants of Oncidium were regenerated after cocultivating protocorm-like bodies with Agrobacterium tumefaciens strain GV3101 containing the vectors pEPYON-42P and pEP-YON-42H with 35S::PMI and 35S::HPTII gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Any results of transformations from previous research indicated that infection period varied from few minutes to few hours, 5 min on Artemisia carvifolia [5]; 30 min on Oncidium Gower Ramsey, Crambe abyssinica , and Dendrobium chrysotoxum Lindl [42], [43], [44]; 40 min on Cordyline fruticosa [45]; an hour on Helianthus tuberosus [46]; 4 h on Erycina pusilla [10]. The results of observation (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Any results of transformations from previous research indicated that infection period varied from few minutes to few hours, 5 min on Artemisia carvifolia [5]; 30 min on Oncidium Gower Ramsey, Crambe abyssinica , and Dendrobium chrysotoxum Lindl [42], [43], [44]; 40 min on Cordyline fruticosa [45]; an hour on Helianthus tuberosus [46]; 4 h on Erycina pusilla [10]. The results of observation (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Using this technique, these authors reported 33-43% PLBs expressing the β-glucuronidase gene (GUS) and obtained six lineages that amplified the transgenes pepper ferredoxin-like protein (pflp) and hygromycin phosphotransferase (hpt) using the particle bombardment technique. Agrobacterium tumefasciens-mediated transformation has also been successfully used in the production of transgenic plants of Oncidium 'Sharry Baby OM8' and Oncidium Gower Ramsey using the induction of secondary PLBs from in vitro-maintained PLBs [148,149].…”
Section: Applications Of Ipr-plb Technique On Orchid Propagation and mentioning
confidence: 99%
“…Timentin TM is one of the most expensive antibiotics used widely in transformation studies (Ieamkhang et al 2005;Slater et al 2011;Thiruvengadam et al 2011). Clavamox Ò is relatively inexpensive and appears to work effectively at a low dose (250 mg l -1 ).…”
Section: Selection For Transformationmentioning
confidence: 99%